POP ART PRINTS AS A CREATIVE SOURCE FOR DESIGNING MODERN CLOTHING COLLECTIONS - Струмінська, Т. В.; Михайлюк, О. Ю.; Слітюк, О. С.; Омельченко, Г. В.; Дегтяр, Т. Ю. (Art and Design, 2020)
The purpose of the work is to determine the main art and compositional solutions of pop art prints of prints for further design of author’s prints and the development of creative collections of modern women’s clothing. To achieve this goal, special features, art and figurative features of pop art style prints were structured, a visual analytical and comparative analytical analysis of the collections of women’s and men’s clothing in the style of pop art for the spring-summer 2019 and 2020 seasons was carried out. Highlighted the characteristic compositional solutions of modern prints in the style of pop art in clothing (lettering; drawings of murals; comics, collages and subject images; lines and color combinations) are highlighted, a comparative analysis of the use of stylistic features of pop art in men’s and women’s clothing collections of spring summer 2019-2020 seasons. Recommendations for the development of prints for promising collections of women’s clothing for the spring-summer 2020 season suggest the use of small images, not on the entire plane of the product, the repetition of individual image elements, it is recommended to use subject image of consumer goods, food, comics or lettering. The scientific novelty lies in the study and systematization of compositional and visual solutions of prints in the style of pop art in the collections of modern fashion designers. Based on the definition of fashion trends and the main art and figurative features of prints in the pop art style, author’s prints and a collection of women’s clothing have been developed.